Management of generalized attrition with an overlay removable partial denture for restoration of the OVDa new treatment option (City Dental College Journal, 2012)
Overlay removable partial denture can be used as an interim prosthesis for the patients who have lost their occlusal vertical dimension due to moderate to severe attrition resulting in functional and esthetic problems. This prosthesis is believed to allow neuromuscular adjustments to a newly adjusted VDO and also to observe the function and esthetics. ORPDs provide reversible and relatively inexpensive treatment for the patients who have limitations. In this case report, a patient was treated with overlay removable partial denture for restoring the lost vertical dimension. This article reviews indication, advantage, disadvantages of ORPDs. Though there are esthetic and functional limitations with potential risk of material fracture, all patients with severely worn dentition with decreased VDO and missing teeth should be offered this treatment option. Regular recall and maintenance visit are essential for long term success of ORPDs.DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11834 City Dental College Journal Vol.9(1) 2012 23-27